Colloidal Perovskite Nanomaterials Processing and Photovoltaic Loss Analysis - Galatopoulos, Fedros; Papagiorgis, Paris; Chrusou, Alexandra; Bernasconi, Caterina; Christodoulou, Constantinos; Bodnarchuk, Maryna I.; Kovalenko, Maksym V.; Itskos, Grigorios; Choulis, Stelios A. (My University, 2022)
In recent years, perovskite nanocrystals (PNCs) have attracted research interest for various optoelectronic applications that include light emitting diodes (LEDs) and solar cells 1. Several inherent material properties are desirable for both applications such as high photoluminescence quantum yield (PLQY), strong light absorption as well as the minimization of radiative recombination losses 2 3. Furthermore, PNCs show relatively high defect tolerance and tunability of the band gap by controlling the size and composition of the nanocrystals 4 5. In this work we compare photovoltaic (PV) devices based on (CH2(NH2))2PbI3 (FAPbI3) and CsPbI3 PNCs capped by oleic acid ligands. Specifically, we evaluate the influence of the processing conditions (ambient versus inert atmosphere and the effect of ligand washing (LW) steps on the photovoltaic (PV) performance of cells based on FAPbI3 and CsPbI3 PNCs. FaPbI3 PNCs shows increase in grain size upon the introduction of a ligand washing (LW) step based on formamidinium iodide (FAI) salt in EtAc due to ligand desorption and subsequent agglomeration of the NCs. Photovoltaic devices based on FAPbI3 PNCs provided a maximum PCE of 1.93% with the introduction of 3 LW steps with formamidinium iodide (FA) dissolved in ethyl acetate (EtAc) while CsPbI3 photovoltaic devices have provided PCE of 1.83 % using the same LW steps. The main photovoltaic performance limitation in both cases is the low Jsc and FF due to the high series resistance (Rs) which indicates oleic acid ligand washing step limitations. The long oleic acid inhibit carrier transport within the NCs and therefore proper LW is essential to ensure good PV performance 6. It was found that photovoltaic devices based on FAPbI3 PNCs show lower PCE when processed in ambient conditions compared to inert conditions, while devices based on CsPbI3 PNCs show similar PCE in both cases. It is important to note that although photovoltaic devices based on CsPbI3 PNCs show similar PCEs in both inert and ambient conditions, the photovoltaic devices that were fabricated in ambient conditions are less reproducible compare to the ones processed in inert atmosphere.